Construction of artificial intelligence-assisted English learning resource query system - Yao, Wenjing; Li, Ning (Frontiers in Psychology, 2022)
English has become an important tool for China's opening to the outside world and exchanges with other countries. More and more people have the motivation and requirements to learn English, but under the traditional English learning mode and traditional teaching mode, the cultivation of learners' autonomous learning habits is ignored. This paper aims to study the construction of artificial intelligence assisted English learning resource query system and establish the relevance feedback mechanism of retrieval. This paper applies this mechanism to the retrieval of learning resources, so as to provide learners with the learning resources they really need and improve learners' learning efficiency. This paper proposes to find the relevant knowledge points by extracting the knowledge points of the retrieval content. It realizes the query expansion based on knowledge, and then realizes the expansion of retrieval results. It realizes the mapping of knowledge points on the retrieval content, the query and expansion of knowledge points, and the presentation of learning resources of knowledge point index. It also uses the relevance feedback mechanism to adjust the retrieval results to meet the retrieval needs of learners. The experimental results show that the number of knowledge points can be increased to 2-4 times by query expansion based on English resources. Thus, the number of learning resources of search results can be increased to 3-10 times, the expansion of search results can be realized, and the overall recall will be greatly improved.In this paper, the related methods of artificial intelligence are applied to the construction experiment of the English learning resource query system, which has a certain promotion effect on the construction of the system.